Pengaruh Permainan Sains Terhadap Perkembangan Kecerdasan Logika Matematika Anak Usia Dini - Siti Marli'ah (JCE (Journal of Childhood Education), 2018)
This study aims to analyze the influence of science playing on the development of mathematical logic intelligence in early childhood. This research is a type of experimental research using nonquivalent control group design. This research was conducted at TK Islam Insan Kamil Tuban with research subject of 40 children divided into control group and experiment group. The research data was collected by observation and documentation technique. Data analysis using ANOVA test or F test. Â The results showed that the science playing has an effect on the development of the mathematical logic intelligence of children. This is evidenced by the difference of mathematical logic result between experimental group that is equal to 70% and control group equal to 58,75%. Furthermore, it is recommended for teachers and institutions of early childhood to apply science play activities as an alternative of learning activities to stimulate the mathematical logic intelligence of children.